1980
DOI: 10.1021/i260074a011
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of the Gas-Phase Catalytic Isomerization of Xylenes

Abstract: The kinetics of the gas-phase isomerization of xylenes in the presence of hydrogen have been studied in a fixed-bed flow reactor under initial conditions. The study was carried out using a silica-alumina catalyst containing 4 wt % nickel, at 400 to 465 °C and a total pressure of up to 3.95 kg/cm2. The kinetic parameters thus obtained when used iri our mathematical model reproduce the observed product distribution up to equilibrium conversion in an isothermal reactor packed with powdered catalyst. By introducin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 7 publications
1
24
0
Order By: Relevance
“…Xylene isomerization is industrially carried out in the gas phase in the presence of hydrogen, over bifunctionaltype zeolite catalysts comprising metal sites that act as hydrogenation sites, to reduce deactivation due to coke and to convert ethylbenzene [3]. On the other hand, Daramola et al [4] observed a reduction of coke formation by reducing diphenylmethane intermediates due to selective p-xylene (PX) extraction in an extractor-type catalytic membrane reactor.…”
Section: Introductionmentioning
confidence: 99%
“…Xylene isomerization is industrially carried out in the gas phase in the presence of hydrogen, over bifunctionaltype zeolite catalysts comprising metal sites that act as hydrogenation sites, to reduce deactivation due to coke and to convert ethylbenzene [3]. On the other hand, Daramola et al [4] observed a reduction of coke formation by reducing diphenylmethane intermediates due to selective p-xylene (PX) extraction in an extractor-type catalytic membrane reactor.…”
Section: Introductionmentioning
confidence: 99%
“…As the reactor is loaded with 1 g catalyst and low conversions are obtained due to high GWHSVs employed, Equation (20) readily calculates the reaction rates without any need to considering total pressure change because of pressure drop or integration over the reactor height. In addition, all experimental data had been taken at steady-state operating conditions where the outlet concentrations were stable (up to 2 h).…”
Section: Kinetic Model Descriptionmentioning
confidence: 99%
“…The activation energy for o-xylene, m-xylene, and p-xylene adsorption was considered to be equal to -16.47 kJ mol −1 based on the pioneering work of Corma and Cortes. 20 The adsorption/desorption activation energy of ethylbenzene was taken -30.09 kJ mol −1 , based on the theoretical prediction of Hansen et al 27 Regarding the transport parameters, the initial guess for the diffusion activation energy of ethylbenzene was set equal to 25.00 kJ mol −1 , according to the work of Nießen and Karge. 28 Tables 1-3 Figure 2 shows a plot of the experimental and model concentrations of different species for a reaction temperature of 390 • C. It should be mentioned that there exists a slight decrease/increase of the experimental concentration of the species under consideration with an increase of GWHSV.…”
Section: Kinetic Model Descriptionmentioning
confidence: 99%
See 1 more Smart Citation
“…This phenomenon is explained by the fast movement of the para isomer inside the porous catalyst which might cause an apparent 1,3 shift of the methyl group in the benzene ring [28]. The second scheme on the other hand, assumes that the reaction proceeds via 1,2-methyl shift only (o-Xylene to m-Xylene to p-Xylene) where one of the methyl groups in m-Xylene might shift to the adjacent positions through a series of consecutive, reversible 1,2-methyl shift mechanism and become o-Xylene or p-Xylene [29][30][31][32][33][34][35].…”
Section: Reaction Modelmentioning
confidence: 99%